The Role of Islamic Counseling Guidance in Improving Emotional Intelligence in the Millennial Generation - Adih, Adih (PT. Anagata Sembagi Education, 2024)
This study aims to examine the influence of Islamic counseling guidance on increasing emotional intelligence in the millennial generation. Millennials, as an age group that often face emotional challenges related to social, academic, and work pressures, need an effective approach to managing their emotions. Islamic counseling guidance, which integrates psychological aspects with spiritual values, is believed to help in overcoming these emotional problems. The type of research used is quantitative with a survey approach, involving 110 randomly selected respondents from the millennial generation who are involved in Islamic counseling guidance activities in educational institutions and Islamic communities. The data was collected using a questionnaire that measured two main variables, namely Islamic counseling guidance and emotional intelligence, with a Likert scale of 5 points. Before the analysis is carried out, a test of the validity and reliability of the research instrument is carried out to ensure the validity and consistency of the data. The data was analyzed using SPSS version 25 through a simple linear regression test to determine the influence of Islamic counseling guidance on emotional intelligence, as well as a t-test to test the significance of this influence. The results of the study show that Islamic counseling guidance has a significant influence on the increase of emotional intelligence in the millennial generation. These findings suggest that a holistic approach in Islamic counseling guidance, which combines psychological and spiritual aspects, can contribute to the development of better emotional intelligence among millennials. This research contributes to the development of more adaptive and effective counseling guidance methods, as well as opening up opportunities for wider implementation in various educational and social contexts